Mapping the intersection of HIV and Alzheimer’s disease: a bibliometric analysis of emerging research trends - Zhang, Hao; Yuan, ShuYou; Bao, HongXia; Chen, WenJun; Cai, Bo; Sun, JunKai; Zhu, HaoGang; Lu, Wei (Frontiers in Neurology, 2025)
BackgroundHIV and Alzheimer’s disease (AD) are significant global health challenges with overlapping neuroinflammatory and protein aggregation mechanisms. Understanding their intersection is critical for advancing therapeutic strategies, particularly in aging populations.ObjectiveThis study aims to provide a comprehensive bibliometric analysis of research trends at the intersection of HIV and AD, identify emerging themes, and highlight key contributors in this interdisciplinary field.MethodsUsing the Web of Science Core Collection, we retrieved 4,856 articles and reviews published between 1994 and 2025. Bibliometric analysis was conducted with VOSviewer, CiteSpace, and R software to examine publication trends, international collaboration, institutional contributions, journal dynamics, author networks, and thematic evolution.ResultsThe analysis reveals a 14.18% annual growth rate in publications, with the U.S. leading in productivity, followed by China, Germany, and Japan. Key institutions include the NIH and the University of California System, while journals such as Journal of Biological Chemistry and PLOS ONE show significant growth. Prominent authors include Masliah, Eliezer, and Heaton, RK. Research highlights the overlap between HIV-associated neurocognitive disorders (HAND) and AD, emphasizing shared mechanisms like neuroinflammation, protein aggregation, and blood–brain barrier disruption. Recent advances focus on cerebrospinal fluid biomarkers, oxidative stress, and the impact of antiretroviral therapy (ART) on neurological outcomes. Studies increasingly explore the role of advanced methodologies, including machine learning, in elucidating shared mechanisms such as neuroinflammation, endoplasmic reticulum stress, and protein misfolding.ConclusionThis bibliometric analysis underscores the dynamic and rapidly evolving research landscape at the intersection of HIV and AD, driven by collaborative efforts and technological advancements. Future research should prioritize longitudinal studies, mechanistic insights, and translational applications to address unanswered questions in this critical field.